Mexico : 2006 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Mexico's two main economic policy challenges are to fully entrench stability and to remove remaining obstacles to economic growth, necessary to end poverty. The floating exchange rate policy continues to serve Mexico well. An essential part of Mexico's stability is the resilience of the financial system. The oil sector poses a policy dilemma, exacerbated by institutional constraints and governance issues. Although the near-term growth outlook remains closely linked to that of the U.S. economy, medium-term growth depends on structural reforms.